2010
DOI: 10.1080/00223891.2010.497396
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Alcohol Expectancy Questionnaire: Confirmatory Factor Analysis, Scale Refinement, and Further Validation

Abstract: The Comprehensive Alcohol Expectancy Questionnaire (CAEQ; Demmel & Hagen, 2003a, 2003b) is a self-report measure designed to assess an individual's alcohol expectancies. In this study, we examined the CAEQ in a student sample (N= 932) and in a clinical sample of alcohol-dependent inpatients (N= 744). The Five-factor structure was confirmed by means of confirmatory factor analysis. Convergent validity of the revised CAEQ was supported by showing significant relationships to quantity and frequency of drinking. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 64 publications
4
30
0
1
Order By: Relevance
“…Previous work suggests that this association may be related to drinking motives (Kuntsche et al, 2006) or expectancies (Ibanez et al, 2015). Although overall the literature on negative alcohol expectancies (such as cognitive or behavioral impairment) is mixed, indicating there may be differing effects of specific expectancies on drinking stage, the current finding mirrors results from Nicolai et al (2010) who found a similar effect in both student and clinical samples.…”
Section: Discussionsupporting
confidence: 69%
“…Previous work suggests that this association may be related to drinking motives (Kuntsche et al, 2006) or expectancies (Ibanez et al, 2015). Although overall the literature on negative alcohol expectancies (such as cognitive or behavioral impairment) is mixed, indicating there may be differing effects of specific expectancies on drinking stage, the current finding mirrors results from Nicolai et al (2010) who found a similar effect in both student and clinical samples.…”
Section: Discussionsupporting
confidence: 69%
“…Drinking expectancies have been identified as important predictors of alcohol use (Fromme and Dunn, 1992; Nicolai et al, 2010), drunk driving (Turrisi and Jaccard, 1992), and RWDD (DiBlasio, 1986; Grube and Voas, 1996). However, we identified only 1 cross-sectional study that examined the association between RWDD-specific expectancies and RWDD behavior (DiBlasio, 1988).…”
Section: Distal Predictors Of Rwddmentioning
confidence: 99%
“…Findings regarding the predictive role of negative AEs in the same populations have been less consistent. Whereas some studies have found a negative association between negative AEs and drinking (e.g., Fromme & D'Amico, 2000;Nicolai et al, 2010), others have found negative AEs to be related to problematic drinking (Zamboanga et al, 2010) or unrelated to drinking and/or problematic drinking (Neighbors et al, 2007;Zamboanga et al, 2006).…”
mentioning
confidence: 99%